Teknologi Media Baru: Perubahan Analog Menuju Digital - Muqsith, Munadhil Abdul (BULETIN ADALAH, 2021)
The current of globalization that flows rapidly to all corners of the world is caused by the development of information and communication technology (ICT), thereby erasing boundaries between countries including distance and time. This paper wants to discuss the change from analog to digital, which of course has a significant impact on human life.Keywords: Analog; Digital; Technology